Expression of a RING-HC protein from rice improves resistance to Pseudomonas syringae pv. tomato DC3000 in transgenic Arabidopsis thaliana - Cheung, Ming-Yan (Journal of experimental botany, 2007)
A cDNA clone (OsRHC1) was obtained, which encodes a novel RING zinc finger protein sharing similar structural features (multiple transmembrane domains at the N-half; a unique RING zinc finger consensus Cys-X(2)-Cys-X(11)-Cys-X-His-X(3)-Cys-X(2)-Cys-X(6)-Cys-X(2)-Cys at the C terminus) to a group of closely related annotated proteins from both monocots and dicots. OsRHC1 was found to be localized on plasma membrane of rice cells and induced by wounding in rice lines containing Xa loci. Ecotopic expression of the OsRHC1 cDNA from rice (a monocot) in transgenic Arabidopsis thaliana (a dicot) enhanced the defence response toward Pseudomonas syringae pv. tomato DC3000, suggesting that OsRHC1 may confer broad-spectrum disease resistance. The protective effects were neutralized in the presence of MG132 or in an npr1-3 mutation background, indicating that the function of OsRHC1 is dependent on the ubiquitin-mediated protein degradation via the 26S proteasome and the presence of the key defence response regulator NPR1